Quantitative infrared analysis of welding processes: temperature measurement during RSW and CMT-MIG welding. (January 2014) - Frappier, R.; Benoit, A.; Paillard, P.; Baudin, T.; Le Gall, R.; Dupuy, T.
<x content-type="archive" xml:space="preserve">Abstract</x> This article deals with temperature characterisation by infrared thermography during welding. To demonstrate the versatility of this technique, two welding processes were investigated with different materials: cold metal transfer metal inert gas welding of al alloy and resistance spot welding of galvanised steel. Two experimental methods were used to characterise temperature without requiring implementation of thermocouples. The validity of these methods is demonstrated by metallurgical characterisations. The error on the measured values of temperature is assessed regarding the initial uncertainty on the apparent surface emissivity. The results show that it is possible to obtain absolute temperature values, cooling rates and informative visualisation of temperature gradients with a reasonable uncertainty.